Pertanggungjawaban Tindak Pidana Pencabulan Anak yang Dilakukan oleh Anak dengan Pendekatan Restorative Justice - Meilin Octaviani Gultom (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This research aims to analyze how criminal responsibility is applied to children who commit acts of sexual abuse, as well as how the restorative justice approach is implemented in resolving such cases. The method used is normative legal research, by analyzing legislation, legal doctrines, and relevant court decisions. The research results show that child offenders can still be held accountable, but the diversion process must be prioritized in accordance with the Child Protection and Juvenile Justice Law (UU SPPA). The restorative justice approach is considered capable of providing a more humane resolution focused on recovery, although there are still obstacles in its application to sensitive cases such as sexual abuse. This research concludes that the mechanism still provides legal certainty and is more proportional for all parties.